Integration of EEG - Zhongming Liu
This article discusses different approaches that have been proposed for multimodal neuroimaging, with special emphasis on the integration of electroencephalography (EEG), magnetoencephalography (MEG), and magnetic resonance imaging (MRI), and functional MRI (fMRI). Some applications will be shown to illustrate the efficacy and importance of these techniques in clinical and neuroscience studies. Finally, some remaining challenges and problems in the multimodal integration will be discussed
Keywords: EEG; MEG; MRI; Clinical studies; Electroencephalography; fMRI; Functional MRI; Magnetic resonance imaging; Magnetoencephalography; Multimodal neuroimaging; Neuroscience